(untitled) (American Journal of Business Management, Economics and Banking, 2025)
The article reveals the relevance and importance of investment risk assessment and management mechanisms in the digital economy, conducts a comprehensive analysis of factors affecting the attractiveness of the investment environment, analyzes the attractiveness of the investment environment: the experiences of developed countries, and provides conclusions and proposals for increasing the attractiveness of the investment environment in our country.